2021
DOI: 10.23968/2500-0055-2021-6-1-19-31
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Traditional Architecture of Lucknow With Reference to Climatic Responsiveness

Abstract: Introduction: Traditional architecture, all over the world, has many characteristics that ensure thermal comfort. In the past, people built their houses in harmony with the environment, while also optimally utilizing the building materials available locally. The traditional built form was climate-responsive; it evolved over centuries of experience and observations of climate and nature. The traditional local architecture of Lucknow (a North Indian historical city) has employed some ingenious natural and passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Courtyard is one of the familiar elements in the regional architectural styles designed to use the sun's warmth and light. It was observed that the traditional courtyard houses of Lucknow, which are compact and self-shaded can limit the daytime indoor temperature rise during summer (4) . Results from quantitative evaluation carried out on the vernacular buildings of Bikaner, India revealed that natural and passive design systems provide comfortable indoor environment irrespective of the outdoor climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Courtyard is one of the familiar elements in the regional architectural styles designed to use the sun's warmth and light. It was observed that the traditional courtyard houses of Lucknow, which are compact and self-shaded can limit the daytime indoor temperature rise during summer (4) . Results from quantitative evaluation carried out on the vernacular buildings of Bikaner, India revealed that natural and passive design systems provide comfortable indoor environment irrespective of the outdoor climatic conditions.…”
Section: Introductionmentioning
confidence: 99%